2008
DOI: 10.11120/ened.2008.03020045
|View full text |Cite
|
Sign up to set email alerts
|

A three year case study of using audio to blend the engineer’s learning environment

Abstract: A blended approach to learning, teaching and assessment has been part of curriculum design in the teaching of software engineering at Sheffield Hallam University since 2003 when the Blackboard virtual learning environment (VLE) was first used alongside lectures and laboratorybased assignments. In seeking a greater degree of integration between physical and virtual learning spaces we have been keen to explore how digital audio can be used to engage and develop students. Digital audio has shown itself to be a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 5 publications
2
14
0
1
Order By: Relevance
“…Making audio recordings of feedback conversations extends the life and value of important conversations by creating new opportunities for the conversation to be revisited later, as determined by the student. This disrupts patterns of learning potentially: students may now expect, or be expected, to reconnect with earlier conversations to examine or reflect on their growth or discover new meanings in the conversation that may have been missed before (Nortcliffe & Middleton, 2008). The introduction of smartphone audio applications, email communication applications and the integration of application functionality has enabled the academic to simplify and increase the efficiency of producing feedback on students' coursework leading to benefits for the academic and student .…”
Section: Smart Device Applications Developed By the Educator For Learmentioning
confidence: 99%
“…Making audio recordings of feedback conversations extends the life and value of important conversations by creating new opportunities for the conversation to be revisited later, as determined by the student. This disrupts patterns of learning potentially: students may now expect, or be expected, to reconnect with earlier conversations to examine or reflect on their growth or discover new meanings in the conversation that may have been missed before (Nortcliffe & Middleton, 2008). The introduction of smartphone audio applications, email communication applications and the integration of application functionality has enabled the academic to simplify and increase the efficiency of producing feedback on students' coursework leading to benefits for the academic and student .…”
Section: Smart Device Applications Developed By the Educator For Learmentioning
confidence: 99%
“…Much of this research has been empirical, with case studies published on the effectiveness of VLEs in enhancing student learning across a range of disciplines, including Accounting (Broad, Matthews & McDonald, 2004; History (Rogers, 2004), Operations Management (Greasley, Bennett & Greasley, 2004), Engineering (Nortcliffe & Middleton, 2008), Foundation year studies (Turney, Robinson, Lee & Soutar, 2009) and Nursing (Moule, Ward & Lockyer, 2010). These studies range from initial experiments with early versions of VLEs (Greasley et al , 2004) to the specific use of a single aspect of learning technology such as audio feedback to engineering students (Nortcliffe & Middleton, 2008). The findings of these studies lend weight to the notion that the student learning experience, but not necessarily the student's grade, is enhanced by the appropriate use of learning technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies by Merry and Orsmond (Merry & Orsmond, 2008) and Nortcliff and Middleton (Nortcliffe & Middleton, 2008) measured the effectiveness of supervisors' RAF and concluded that learners perceived and implemented audio file feedback in different and more meaningful ways than they did written feedback. Audio feedback has also been noted as bridging a gap between the learner and the supervisor and being a time-saver for the supervisor (Schwartz & Gurung, 2012;Gould & Day, 2013;Ice, Curtis, Phillips, & Wells, 2007;Lunt & Curran, 2010;Munro & Hollingworth, 2014;McCarthy, 2015).…”
Section: Related Workmentioning
confidence: 99%